A comparative study of the application of two horse welfare assessment protocols. (2nd January 2016) - Viksten, S. M.; Visser, E. K.; Blokhuis, H. J.
ABSTRACT: Two assessment protocols for horse welfare were compared: the Swedish official protocol (OP) and a newly developed horse welfare assessment protocol (HWAP). The protocols differ in composition: the HWAP contains 20 animal-based (35.7%), 28 resource-based (50.0%) and 8 management-based (14.3%) measures whereas the OP has 4 animal-based (8.9%), 21-resource-based (46.7%), 16-management-based (35.6%) and 4-uncategorized measures (8.9%). The HWAP detected more welfare issues than the OP for 11 out of 12 welfare criteria. The OP took less time to assess (2–4 h) compared to the HWAP (3 h 20 min to 8 h 40 min). The added level of detail and more animal-based measures means that the HWAP provides a more thorough assessment of welfare of the individual animal than the OP.